Maintaining Organizational Sustaincapability Towards Management Innovation Using Strategic Foresight - Wimber Jerry Panjaitan; Erlinda Sholihah; Iwan Koerniawan; Myra Andriana (University of Science and Computer Technology, 2022)
This study aims to examine the role of Strategic foresight and its capability to support the development ofmanagement innovation processes within organizations. This study uses a narrative literature review approachinvolving potential interactions of three main topics, namely: strategic foresight, management innovation, andmanagement cognition. The research findings explain that every individual has a character from birth to beingable to see the future. Then the capability for foresight in this organization must be developed and continuouslymaintained by both stakeholders in the organization's management and employees. Before implementing afoiresight strategy, it is necessary to understand in depth managerial cognition as the basis for its application.Furthermore, the development of a well-managed strategic foresight will become a management innovation sothat it can maintain the sustaincapability of the organization. This conceptual paper lays a foundation that can beused as further research in determining strategic foresight abilities in relation to managerial dynamic abilities. Theresults of this paper can be used by organizations with a long history of facing challenges in capturing thechallenges of changing business environment in the future.